(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2006)
Based on previous investigations that analysed therapists’ verbalizations, the present study has adopted both a reviewed system of categories regarding basic functions of therapists’ verbalizations, and prior reading of transcriptions as familiarization strategy in order to evaluate (a) the effect of training on categorizers’ performances; (b) the effect of familiarity induced by prior reading of transcriptions on agreement; and (c) the cumulative effect of continued exposure to the categorization task. Results demonstrate that exposure to training (but not prior reading) produces higher percentages of agreement, although they are insufficient for validating the categorization system. Results also suggest that the complexity of categorized sessions is a variable that infuences percentages of agreement. Furthermore, some consistent category overlappings suggest the need of further review of the adopted categorization system.